Synchronous Fluorescence Spectroscopic Technique: The Tool for Rapid Identification of Polycyclic Aromatic Hydrocarbons (PAHs) at Sub-ppm Level in Liquid Samples - Apisit Songsasen; Sornnarin Bangkedphol; Pornpun Pornsinlapatip (Agriculture and Natural Resources, 2002)
Various polycyclic aromatic hydrocarbons (PAHs) at sub-ppm level were identified qualitatively by synchronous scanning fluorescence technique at various wavelength intervals (Δλ). Due to the difference in chemical structure, each PAHs gives specific characteristic spectrum for each wavelength intervals (Δλ). This work demonstrated that the synchronous scanning fluorescence method can be used as a tool for the rapid identification of PAHs in ethanolic sample which contain three or six types of PAHs such as fluorene, truxene, benzo(k) fluoranthene, carbazole, chrysene, anthracene, acenaphthene and indeno(1,2,3,cd)pyrene in mixture.